Perspectives on COVID-19 prevention and treatment using herbal medicine in Vietnam: A cross-sectional study - Tran, V. D.; Pham, D. T.; Cao, T. T. N.; Bahlol, M.; Dewey, R. S.; Le, M. H.; Nguyen, V. A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. The significance of herbal medicine (HM) during the COVID-19 pandemic has been confirmed. Nevertheless, limited studies have included the people perspectives on COVID-19 prevention/treatment using herbal medicine in Vietnam. Thus, this study tackled the aforementioned issue. Methods. Online-based cross-sectional study was conducted in Vietnamese adults between FebruaryApril 2021. Descriptive analysis, regression and Chi-squared tests were implemented for the statistical purposes. Results. A total of 787 respondents attended the study, 368 (46.8%) confirmed that they use herbal medicine/ nutritional supplements for COVID-19 prevention/treatment. Over 50% of the respondents possessed positive perspective on vitamin C ingestion. Using herbal medicine for external use as a disinfectant was mostly preferred. Respondents who had a ‘very good’ health self-perception or who lived in rural areas, were more likely to have a positive opinion in the COVID-19 prevention/treatment using herbal medicine. The main barrier for herbal medicine utilization was the deficiency of personal experience or expert advice. Conclusion. The Vietnamese people commonly utilize herbal medicine for the COVID-19 prevention/ treatment. These data might help policy-makers in managing the public knowledge and practice on herbal medicine use in Vietnam.